1998
DOI: 10.1046/j.1365-2672.1998.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the biocide susceptibility of Staphylococcus epidermidis and Escherichia coli cells associated with rapid attachment to plastic surfaces

Abstract: GI LB E RT . 1998. Differences in opacity between wells of a microtitre plate containing different volumes of inoculated growth medium reflected planktonic growth without any contribution from cells attached at the well surface. Simple algebra and a knowledge of the dependence of optical density upon sample path length (volume) for suspensions of differing cell density enables the generation of growth curves for attached populations (biofilms). In this manner, minimum inhibitory concentrations (MICs) were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 14 publications
2
94
0
Order By: Relevance
“…This system has been heavily used to identify potential anti-biofilm agents, by measuring the reduction in surface attached biomass on the sides of wells after treatment with potential therapeutic agents [51][52][53][54]. In addition to this, The Center for Disease Control (CDC) approved biofilm reactor [55][56][57], and drip flow reactors, have proved excellent for assessing biofilm formation on biological and non-biological materials [58][59][60].…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…This system has been heavily used to identify potential anti-biofilm agents, by measuring the reduction in surface attached biomass on the sides of wells after treatment with potential therapeutic agents [51][52][53][54]. In addition to this, The Center for Disease Control (CDC) approved biofilm reactor [55][56][57], and drip flow reactors, have proved excellent for assessing biofilm formation on biological and non-biological materials [58][59][60].…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…Research by Zhou et al [12] indicates that low PHMG concentrations only damaged the external structures of bacterial cell membrane. Das et al [13] determined the ability of E. coli and S. aureus to form biofilm on polymers with incorporated polyhexamethylene biguanide in the presence of acetic acid. Their research demonstrated that PHMG inhibits biofilm formation and reduces bacterial cells adhesion to polymer surfaces, which is beneficial in packaging and medical industries.…”
Section: Resultsmentioning
confidence: 99%
“…In planktonic cells biooxidation was totally inhibited in the presence of 25 ppm glutaraldehyde while biofilms retained some of their bio-oxidation capacity in the presence of glutaraldehyde up to 180 ppm. This may be attributed to the effect of exopolysaccharide polymers produced as a potential barrier which can prevent biocides from reaching the target organisms within the biofilms (Das et al 1998;Morton et al 1998;Stewart et al1998). It can be assumed that in the presence of biocide planktonic bacteria play no part in the substrate removal and only bio-oxidation by the biofilms takes place.…”
Section: Susceptibility Changes Of Cells To the Bactericidal Activitymentioning
confidence: 99%
“…Biofilm formation causes reductions in efficiency in industrial machinery, heat exchangers, vessels and filters (Melo and Bott, 1997;Bott, 1998;Das et al 1998) and may cause acceleration of metallic corrosion (Cloete et al 1998). Numerous methods have been used for minimizing adverse effects of biofilm formation.…”
mentioning
confidence: 99%